Thermal assessment of TN28VT flasks carrying vitrified residue while under transport in PNTL's Pacific Grebe. (December 2013) - Egarr, D. A.; Burt, D.; Cory, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The Pacific Grebe is one of Pacific Nuclear Transport Ltd's fleet of ships and is managed by International Nuclear Services Ltd. She is an Irradiated Nuclear Fuel (INF) 3 certified vessel under the INF code of the International Maritime Organization. This means the Pacific Grebe is certified to carry irradiated nuclear fuel, vitrified residues or plutonium with no restriction of the maximum aggregate activity of the materials. The Pacific Grebe entered full service in 2011, commencing a maiden operational voyage to Japan on August 3 with a shipment of vitrified residue from spent fuel reprocessing. This was the first shipment of vitrified residue following the tsunami that struck Japan's northeast coast in March 2011. The residue product was transported inside TN28VT flasks within the Grebe's cargo holds. There are four holds, each capable of transporting a number of flasks. To support the safety case, thermal assessments were undertaken to determine the following: resin temperatures in the TN28VT flask to demonstrate whether the resin is maintained below the limiting temperature when transporting the maximum heat load of 40·88 kW; the hold air temperature as measured by two thermocouples, which would be used as a control in the Shipment Approval Certificate; and the average hold air temperature to determine whether it was within the limit of 55°C specified by the INF code. The paper describes the work undertaken, which required computational fluid dynamics with conjugate heat transfer and a bespoke one-dimensional heat transfer calculation to determine the thermal boundary conditions at the hold walls.